Quality of life and productivity of employees in the home office work modality: case study in an educational institution in the region of Hortolândia, SP, Brazil - Silva, Élida Taina da; Silva, Allyk de Moura; Gonçales Filho, Manoel (Brazilian Journal of Production Engineering, 2022)
This case study analyzes the quality of life and productivity of employees in the home office modality in an educational institution in the city of Hortolândia, SP, Brazil. The research has a qualitative approach, a comparative method and the technical procedure used is the case study. The results identified in the modality are an increase in the costs of the employee’s residence, an increase in household chores and a lack of computer infrastructure and ergonomics. However, it was identified a better quality of life and productivity growth in the home office.